Variation order contribute to delay / Mohd Azizi Jamil A. Aziz - A. Aziz, Mohd Azizi Jamil (2004)
Construction is among the first economic sector that is affected when there is an economic turmoil. The sector is said to be an economic barometer - the rapidity, slow and steady pace of activity in the industry to a certain extent gives a reflection on the overall economic condition of the country. On 2001, when the country was afflicted by the contagious effect of the global economic slowdown, the government took drastic measures to pump- prime the economy by injecting fund into the construction industry. Over RM 7 billion was allocated for infrastructure project, construction and renovation of school, living quarters and office buildings. Under the 2002 budget, RM 1.08 billion was allocated for the construction of the quarters and more development project were created for rural development – giving equally sufficient job for the big and the smaller players in the industry (Datuk Hj. Abdul Rahman Abdullah, CIDB news, CIDB Malaysia, June 2002, page 3)